2017
DOI: 10.1111/1471-0528.15014
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of antenatal corticosteroids in preterm twins: the EPIPAGE‐2 cohort study

Abstract: Objectives To investigate the efficacy of antenatal corticosteroid (ACS) therapy on short‐term neonatal outcomes in preterm twins, and further document the influence of the ACS‐to‐delivery interval. Design EPIPAGE‐2 is a nationwide observational multicentre prospective cohort study of neonates born between 22 and 34 completed weeks of gestation. Setting All French maternity units, except in a single administrative region, between March and December 2011. Population A total of 750 twin neonates born between 24 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
26
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(26 citation statements)
references
References 35 publications
0
26
0
Order By: Relevance
“…In contrast, two retrospective studies with large samples11 23 and one with a small sample of twins24 reported that the administration of ACS had a protective effect against adverse perinatal outcomes in both singletons and twins born preterm. Also, in a nationwide observational multicentre prospective cohort study of twins born between 22 and 34 completed weeks of gestation in 2011 in France, ACS administered ≤7 days prior to delivery were reported to be significantly associated with a reduced rate of in-hospital mortality 25…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, two retrospective studies with large samples11 23 and one with a small sample of twins24 reported that the administration of ACS had a protective effect against adverse perinatal outcomes in both singletons and twins born preterm. Also, in a nationwide observational multicentre prospective cohort study of twins born between 22 and 34 completed weeks of gestation in 2011 in France, ACS administered ≤7 days prior to delivery were reported to be significantly associated with a reduced rate of in-hospital mortality 25…”
Section: Discussionmentioning
confidence: 99%
“…Also, in a nationwide observational multicentre prospective cohort study of twins born between 22 and 34 completed weeks of gestation in 2011 in France, ACS administered ≤7 days prior to delivery were reported to be significantly associated with a reduced rate of in-hospital mortality. 25 …”
Section: Discussionmentioning
confidence: 99%
“…For bias due to selection of participants, six studies [7][8][9]19,20,27 were at serious risk from restricting to neonates admitted to NICUs (because admission to NICU is related to antenatal corticosteroids and adverse neonatal outcomes). One study 26 included neonates admitted to NICUs and restricted to neonates with very low birth weight (less than 1,500 g), which we rated as moderate risk of selections bias © 2022 by the American College of Obstetricians and Gynecologists.…”
Section: Resultsmentioning
confidence: 99%
“…Some studies reported that antenatal corticosteroids also improved neonatal outcomes in twin preterm births before 34 weeks [13, 18, 19]. Based on these evidences and effectiveness of corticosteroids in preterm singleton pregnancy, ACOG recommends that one course of antenatal corticosteroids should also be used in multifetal pregnant women who are at risk of early preterm birth (before 33 6/7 weeks of gestation) [15, 20].…”
Section: Introductionmentioning
confidence: 99%
“…Second, the results of some retrospective studies on the effectiveness of antenatal corticosteroids in preterm twin neonates were conflicting. Some studies reported that the effect of antenatal corticosteroids on neonatal outcomes in twin pregnancy was comparable with that in singleton pregnancy [13, 18, 19, 21]. However, there are disagreements as to the effect of antenatal corticosteroids in twin pregnancies [22, 23].…”
Section: Introductionmentioning
confidence: 99%